The celiac disease: risk management in foodservice - Gulino, Margherita; Maggi, Claudio; Strumia, Caterina; Caputo, Marcello; Costa, Anna; Mortara, Marina; De Luca, Ilaria; Minutolo, Monica; Amelio, Cinzia; Fornuto, Alessandra; Della Torre, Angelina; Antonioli, Emiliano; et al. (Progress in Nutrition, 2016)
Celiac disease (CD) is one of the most common autoimmune disease that occurs in susceptible individuals after the gluten ingestion, triggering chronic inflammation of the duodenum mucous membrane. In Italy celiac disease it is the most common food intolerance with an estimated prevalence of about 1%, considering both the adults and children category. Currently the only available therapy for celiac disease is the exclusion from the diet of all foods containing gluten and is therefore essential to prevent any contamination. The Italian national legislation (Law no. 123 of 4 July 2005) recognizes celiac disease such as a social disease and prepare interventions for private and public foodservice. Given the importance and spread of CD the Piedmont Region has funded several research projects (in 2013) in collaboration with some Hospital departments (Complex Structure of Aliments Hygiene and Nutrition (SCIAN)), and contributing to the development of a “Projects for the development of the measures implemented by the SCIANs to protect the patients with celiac disease. “. Among the various activities planned in this project there was monitoring of gluten-free meals in the province of Turin (from local health authority called ASL TO5). Specifically, in this study, we verified the canteens of some food service structures, as regards the risk of gluten contamination, during all phases of food processing and preparation (supply, storage, preparation and administration). The analysis and comparison of all monitored structures revealed that school canteens would seem more attentive to the management of the gluten-free meal. Nevertheless, in the canteens of other structures monitored there has been an improvement in the management of the gluten-free meals after the local health authority interventions (ASL TO5), demonstrating the effectiveness of information and education carried out by health staff on the territory.